Customer experience personalization in fashion e-commerce through virtual fitting rooms - Sartortt, M. (2021)
With the constant development of the digital retail market, competition makes it necessary to implement services that increase consumer attractiveness and loyalty. Easy return policies, although attractive, generate charges to tenants, making size recommendation systems essential mechanisms in the maintenance of reverse logistics metrics. This article seeks to contextualize the need for personalization of the consumer experience, through personalized recommendations, also presenting the solution of the company Sizebay. For this, the consumer experience personalization, recommendation systems for fashion e-commerce and the proposed tool as a solution are described. Finally, real data of stores that use the service are presented in order to quantify the impact of personalized recommendations. Through this study it was realized that this practice generates optimizing results, but there is the challenge of greater engagement with consumers with the tool.